2005
DOI: 10.1128/jvi.79.2.1154-1163.2005
|View full text |Cite
|
Sign up to set email alerts
|

Antigenicity and Immunogenicity of a Synthetic Human Immunodeficiency Virus Type 1 Group M Consensus Envelope Glycoprotein

Abstract: Genetic variation of human immunodeficiency virus (HIV-1) represents a major obstacle for AIDS vaccine development. To decrease the genetic distances between candidate immunogens and field virus strains, we have designed and synthesized an artificial group M consensus env gene (CON6 gene) to be equidistant from contemporary HIV-1 subtypes and recombinants. This novel envelope gene expresses a glycoprotein that binds soluble CD4, utilizes CCR5 but not CXCR4 as a coreceptor, and mediates HIV-1 entry. Key linear,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
176
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(181 citation statements)
references
References 36 publications
4
176
1
Order By: Relevance
“…[3][4][5][6][7] These optimization strategies can lead to improved, cross-reactive immune responses. 8,9 The addition of co-delivered gene-based molecular adjuvants is another area in which an augmentation of resulting immune responses frequently occurs. Despite the improvements in vector design and the use of molecular adjuvants, there is still a clear requirement for an efficient method of administration of DNA vaccines that results in high-level expression of the plasmid in the desired cell type of the desired tissue, most commonly, muscle, tumor or skin.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] These optimization strategies can lead to improved, cross-reactive immune responses. 8,9 The addition of co-delivered gene-based molecular adjuvants is another area in which an augmentation of resulting immune responses frequently occurs. Despite the improvements in vector design and the use of molecular adjuvants, there is still a clear requirement for an efficient method of administration of DNA vaccines that results in high-level expression of the plasmid in the desired cell type of the desired tissue, most commonly, muscle, tumor or skin.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, recent research from our lab and others have indicated that utilization of "centralized" immunogens such as consensus immunogens or ancestral immunogens could increase the breadth of cellular immune responses than native DNA immunogens (21,22,25,26). Such consensus immungens in the context of HPV may appear more foreign and thus facilitate immune stimulation, which is an important issue with a slow growth that may induce peripheral tolerance.…”
mentioning
confidence: 99%
“…Consensus and ancestral envelope proteins retained folding and conformational antibody-binding characteristics, and responses to a consensus sequence showed enhanced B-and T-cell cross-reactivity compared with natural strains (DoriaRose et al, 2005;Gao et al, 2005;Santra et al, 2008).…”
Section: Introductionmentioning
confidence: 99%